Implementasi Program Badan Usaha Milik Desa (Bumdes) Dalam Upaya Pengelolaan Potensi Desa(Studi Kasus Bumdes Margo Sejahtera Desa Margomulyo Kecamatan Juwana Kabupaten Pati) - Alya Fajriyati; Augustin Rina Herawati; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The Village Owned Enterprise Program (BUMDes) is one of the government programs that aims to improve the village economy and the welfare of rural communities by utilizing village assets and potential. This study discusses the implementation of Village Owned Enterprises (BUMDes) in an effort to manage village potential in Margomulyo Village, Juwana District, Pati Regency. This study aims (a) to analyze the implementation of the Village Owned Enterprise (BUMDes) program in Margomulyo Village, Juwana District, Pati Regency in an effort to manage village potential; (b) to analyze the obstacles in implementing the Village Owned Enterprise (BUMDes) program in an effort to manage village potential in Margomulyo Village, Juwana District, Pati Regency. The research method used is descriptive qualitative with data collection techniques from interviews, observations and documentation. In addition, researchers try to describe the phenomenon of research in depth using primary and secondary data. The theory used is the implementation theory of Van Horn and Van Meter. The results of this study are the implementation of the BUMDes program in the village of Margomulyo in an effort to manage village potential has not been implemented properly. This is evidenced by the fact that the BUMDes business unit has not been able to have an impact in increasing Village Original Income (PAD). The inhibiting factor for the implementation of the BUMDes program in Margomulyo village is the lack of readiness of the village government and BUMDes managers because the formation of BUMDes Margomulyo is not based on the needs of the village community, but there is a little coercion from the district government. With all the limitations, BUMDes Margomulyo has not been able to establish a business unit by exploiting the potential of the village and is only able to establish one business unit, namely the sale of bottled drinking water. The quality of human resources that are still standard plus the minimal amount of capital has not been able to develop the BUMDes business unit. In addition, the lack of socialization to the community has resulted in the BUMDes program in Margomulyo village not getting support from the community. So that the implementation of the BUMDes program in Margomulyo village was not carried out properly.